2018
DOI: 10.21873/anticanres.12446
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 and PD-L1 Up-regulation Promotes T-cell Apoptosis in Gastric Adenocarcinoma

Abstract: This study provides evidence for a new therapeutic target in gastric adenocarcinoma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 23 publications
1
16
0
1
Order By: Relevance
“…It has been reported that anti-PD-1 antibody enhanced chemokine expression in tumors and T cell infiltration 24,40 . Others have also reported that anti-PD-1 antibody inhibited T cell apoptosis, and enhanced the proliferation of T cells 41 . According to these reports and our current data, we believe that anti-PD-1 antibody treatment induces the infiltration and accumulation of TAS0314-specific CTLs in the tumor microenvironment, which contributes to the synergistic antitumor effects.…”
Section: Discussionmentioning
confidence: 95%
“…It has been reported that anti-PD-1 antibody enhanced chemokine expression in tumors and T cell infiltration 24,40 . Others have also reported that anti-PD-1 antibody inhibited T cell apoptosis, and enhanced the proliferation of T cells 41 . According to these reports and our current data, we believe that anti-PD-1 antibody treatment induces the infiltration and accumulation of TAS0314-specific CTLs in the tumor microenvironment, which contributes to the synergistic antitumor effects.…”
Section: Discussionmentioning
confidence: 95%
“…It is known that PD-L1 plays an important role in tumor development. PD-L1 has been speculated to play a major role in suppressing the immune system that allows immune escape of tumor cells [ 36 40 ]. Multiple researches show that PD-L1 is correlated with the progression of gastric cancer [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple researches show that PD-L1 is correlated with the progression of gastric cancer [ 40 ]. For example, PD-L1 is highly expressed in gastric cancer tissues and associated with a poor prognosis in patients with gastric cancer [ 36 , 41 ]. Overexpression of PD-L1 in peripheral blood may offer an immunological predictor of tumor progression and disease outcome in patients with gastric cancer [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…All data were analyzed using SPSS 15.0 for Windows 39 , 40 . Each experiment was performed in duplicate, and average values were used for quantification.…”
Section: Methodsmentioning
confidence: 99%